2022
DOI: 10.1007/s11426-022-1333-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements of photo- and electro-active hydrogen-bonded organic frameworks

Abstract: The development of hydrogen-bonded organic frameworks (HOFs) with predictable topologies and robust structures for targeted functionality was initially hindered by the relatively weak H-bonding interactions as many HOFs would collapse upon guest solvent removal. Recently, the design of tectons with large π-conjugated systems that form intermolecular shape-fitted π-π stacking interactions has proven to be an effective strategy to create chemically and thermally stable HOFs. More importantly, these HOFs with lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 119 publications
0
17
0
1
Order By: Relevance
“…In this context, a growing number of robust HOFs with permanent porosity has been synthesized, and HOFs may also be considered as raw precursors that can be combined with other functional materials to fabricate multifunctional composite materials. Of late, some excellent reviews about the synthesis and applications of HOFs were also reported. In this Outlook, we would like to summarize the basic principles for the design and construction of robust HOFs. Emphasis was put on the discussion about recent impressive progress in the application of HOFs.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a growing number of robust HOFs with permanent porosity has been synthesized, and HOFs may also be considered as raw precursors that can be combined with other functional materials to fabricate multifunctional composite materials. Of late, some excellent reviews about the synthesis and applications of HOFs were also reported. In this Outlook, we would like to summarize the basic principles for the design and construction of robust HOFs. Emphasis was put on the discussion about recent impressive progress in the application of HOFs.…”
Section: Introductionmentioning
confidence: 99%
“…HOFs are widely used as emerging multifunctional substances in gas storage and separation, [67][68][69][70] molecular sensing, [71][72][73][74] heterogeneous catalysis, [75][76][77][78] biological applications, [79][80][81] photoluminescent materials, [82][83][84][85][86] proton conduction [87][88][89][90][91][92] and membranebased applications. [93][94][95][96] To date, although there have been some reviews on the preparation and application of HOFs, [97][98][99][100][101] reviews on proton conductivity are relatively rare. As far as we know, there is only one review on the proton conductivity of HOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from inherent features of hydrogen-bonding interactions, such as reversible, weak, and poorly directional, HOFs are endowed with the advantages of recyclability, flexibility, and structural diversity. [43][44][45] More importantly, the presence of unpaired and residual hydrogenbonding donor and acceptor groups in the HOFs structure enables the incorporation of functional species into their framework through the facile coordination post-synthetic modification (PSM) method. [46,47] These factors provide motivation for the development of Ln@HOFs material through the modification of HOFs with lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%